Growth of ZnO nanowires on nonwoven polyethylene fibers - Sunandan Baruah et al (Science and Technology of Advanced Materials, 2008)
We report the growth of ZnO nanowires on nonwoven polyethylene fibers using a simple hydrothermal method at a temperature below the boiling point of water. The ZnO nanowires were grown from seed ZnO nanoparticles affixed onto the fibers. The seed ZnO nanoparticles, with diameters of about 6–7 nm, were synthesized in isopropanol by reducing zinc acetate hydrate with sodium hydroxide. The growth process was carried out in a sealed chemical bath containing an equimolar solution of zinc nitrate hexahydrate and hexamethylene tetramine at a temperature of 95 °C over a period of up to 20 h. The thickness and length of the nanowires can be controlled by using different concentrations of the starting reactants and growth durations. A 0.5 mM chemical bath yielded nanowires with an average diameter of around 50 nm, while a 25 mM bath resulted in wires with a thickness of up to about 1 μm. The length of the wires depends both on the concentration of the precursor solution as well as the growth duration, and in 20 h, nanowires as long as 10 μm can be grown. The nonwoven mesh of polyethylene fibers covered with ZnO nanowires can be used for novel applications such as water treatment by degrading pollutants by photocatalysis. Photocatalysis tests carried out on standard test contaminants revealed that the polyethylene fibers with ZnO nanowires grown on them could accelerate the photocatalytic degradation process by a factor of 3.